Use of Local Seismic Network in Analysis of Volcano-Tectonic (VT) Events Preceding the 2017 Agung Volcano Eruption (Bali, Indonesia) - Sahara, David P.; Rahsetyo, Puput P.; Nugraha, Andri Dian; Syahbana, Devy Kamil; Widiyantoro, Sri; Zulfakriza, Zulfakriza; Ardianto, Ardianto; Baskara, Aria W.; Rosalia, Shindy; Martanto, Martanto; Afif, Haunan (Frontiers in Earth Science, 2021)
After more than 50 years of slumber, Agung volcano on Bali Island erupted explosively, starting on November 21, 2017. The eruption was preceded by almost two months of seismic crisis. Our study provides the first analysis of VT events using data from eight local seismic stations deployed by the Center for Volcanology and Geological Hazard Mitigation of Indonesia (CVGHM) to monitor the Agung Volcano activity. In total, 2,726 Volcano-Tectonic (VT) events, with 13,023 P waves and 11,823 S wave phases, were successfully identified between October 18 and November 30, 2017. We attempt to increase the accuracy of the hypocenter locations of these VT events, using a double-difference (DD) relative relocation and a new velocity model appropriate to the subsurface geological conditions of Agung volcano. We found two types of seismicity that represent the VT events relating to fracture network reactivation due to stress changes (during seismic crisis) and off-axis magma intrusion (after seismic crisis). The characteristics of each event type were discussed in terms of Vp/Vs value, phase delay times, and seismic cluster shapes. Waveform similarity analysis was performed to further characterize VT events during the seismic crisis. An interpreted layer which prohibited the magma migration toward the Agung summit during the seismic crisis was deduced based on the spatio-temporal distribution of the seismic events. These findings might explain the long delay (~10 weeks) between the onset of the seismic crisis and the first eruption in 2017. The distinction between both event types observed in this study is significant for eruption forecasting and understanding the subsurface structure of the magmatic system. Based on the results obtained in this study, we emphasize the importance of speedy seismic analysis (location and basic seismic characteristics) of the seismic crisis preceding the Agung volcanic eruption.